Аналіз причин звертальності за стоматологічною допомогою населення працездатного віку - Клименко, Вікторія Іванівна; Смірнова, Ірина Віталіївна; Любомирська, Таісія Ростиславівна; Klimenko, V. I.; Smirnova, I. V.; Lubomirskaya, T. R. (My University, 2013)
The reasons of working people appeals for medical dentistry help in the State municipal organization are analysed. It was found, that the leading reasons are the acute state: defective seals and acute pain. The prophylactic visit to the dentist was performed among (2,97±1,19) % of population. It is determined, that today the prevalence of the private medical dentistry help transformed the structure of the reasons of appeal to the medical help. As a result of this situation the preventive work among population is absent.
The analysis of the reasons of working age people appeals to medical dentistry hel
Keywords: стоматологічна допомога; звертальність; причини відвідування стоматолога-терапевта; medical dentistry help; appeals to medical help, reasons of appeals to dentist; reasons of appeals to dentist